GASTRODIPLOMASI THAILAND TERHADAP INDONESIA DALAM MENINGKATKAN CITRA WISATA MELALUI KITCHEN OF THE WORLD - Tika, Anisya; Fuadi, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Thailand is known as a country that is strong in sex tourism. To change the image of Thai tourism, the Thai government is carrying out Gastrodiplomacy using soft power, because typical Thai food is able to change the image of the country from sex tourism to culinary tourism. Gastrodiplomacy is part of public diplomacy and cultural diplomacy that uses food as a medium for cross-cultural communication. Thai gastrodiplomacy was officially issued in 2002 by the Thai government and was the first country to carry out gastrodiplomacy through the "Kitchen of the World" program on the grounds that the Thai government was implementing the program to become one of the exporters of the agricultural sector in the world, as well as changing the bad image of Thailand as a tourist country. sex. Indonesia is among Thailand's goals in implementing gastrodiplomacy that achieves targets. The perspective that researchers use is the Constructivism perspective. Meanwhile, the theories and concepts used in this research are Gatrosiplomasi and Nation Branding. This research uses qualitative research methods by collecting primary and secondary information. Primary data was obtained through interviews with various parties and secondary data through web-based literature research that supports research. The results of this research show that Thai gastrodiplomacy in Indonesia is going well. The event organizing strategy is the most dominant strategy which is able to attract 20,000 visitors. And Indonesia has benefited greatly from Thai gastrodiplomacy, both from the government and business players. Keywords: Gastrodiplomacy, Indonesia, Thailand: Kitchen of the World.